Total anomalous pulmonary venous drainage in infancy. Issue 4 (April 1977) - Clarke, D R; Stark, J; De Leval, M; Pincott, J R; Taylor, J F
Abstract : Between May 1971 and December 1975, 39 infants had operations for correction of total anomalous pulmonary venous drainage. Fourteen of the 39 patients were under 1 month of age at the time of operation. Twenty-four patients had supracardiac, 7 intracardiac, and 6 infracardiac total anomalous pulmonary venous drainage, and 2 had a mixed type. The overall hospital mortality was 36 per cent. There have been no late deaths. The improvement in survival rate in this series is attributed to: (1) earlier recognition and prompt referral, (2) an aggressive approach to diagnosis involving complete cardiac catheterisation and angiocardiography, (3) vigorous preoperative care, (4) early complete correction including construction of a large anastomosis and enlargement of the left atrium when indicated, and (5) intensive postoperative management paying particular attention to fluid balance and treatment of pulmonary complications. Operative mortality was highest in patients with total anomalous pulmonary venous drainage directly to the superior vena cava, and in those with infradiaphragmatic drainage of whom all had pulmonary venous obstruction. Mortality was not closely related to age, body weight, or severity of pulmonary hypertension.